HYPERBOLIC MODEL OF NON -STATIONARY THERMAL CONDUCTIVITY - E. M. Kartashov; I. V. Antonova (Тонкие химические технологии)
The article presents fundamentally new results on the analytical theory of thermal conductivity for hyperbolic transport models. The questions of the correct formulation of boundary value problems are considered. A technique for finding exact analytical solutions of a rather complex class of boundary value problems based on the method of Green's functions and operational calculus is developed.